Sibstream - Lezhava, Ilya (project baikal, 2016)
The article reviews a new paradigm for the arrangement of settlement systems in Russia. It is proposed to cover the territory of Russia with linear settlement systems, basing mostly on the existing and planned railroads. The author believes that some of the railroads should be turned into large transport corridors, along which wide settlement corridors with cities, agricultural zones, plants, offices, universities, scientific centers, recreations, leisure centers, as well as zones of nature reserves can be organized. The main settlement corridor should be formed along the Trans-Siberian Railway. The author calls this railroad and the adjoining settlement corridor ‘Sibstream’. He proposed to start the Sibstream from the railroad ‘Petersburg-Moscow’ and then to go along the Trans-Siberian Railway. Besides, the article contains several proposals on arrangement of new transport corridors in Siberia, the North of the Arctic Circle, the Far East and Kamchatka, as well as along the railroads planned by the Russian Railways for the long term.
Keywords: paradigm; transport corridor; settlement corridor; the Trans-Siberian Railway; small towns; adjoined territories; ecological settlements